The visible wall : Jews and other ethnic outsiders in Swedish film - Wright, Rochelle, 1950- (Carbondale : Southern Illinois University Press, 1998)
Rochelle Wright provides the first historical overview and analysis of the manner in which Jews and other ethnic outsiders have been depicted in Swedish film from 1930 to the present. Focusing on films produced in Sweden for primarily Swedish audiences, Wright analyzes how the portrayal of the relatively small Jewish minority has evolved over the years. She compares the images of Jews in Swedish film with those of other ethnic subcultures: long-term resident communities such as "tattare "(travelers, an indigenous pariah group often confused with gypsies), Finns, the Sami, and recent immigrant populations such as Greeks, Italians, Turks, and Yugoslavians. Wright s cross-disciplinary approach to interrelated issues of ethnicity and national identity enables her to take advantage of the methodologies of historians and sociologists as well as those of literary and film critics. She bases her study on a detailed analysis of the films, but, by way of comparison, she examines filmscripts and literary sources. She also consults contemporary reviews, interviews with actors and directors, and biographies and memoirs as well as critical discussion among film historians. Wright confronts importantand exceedingly difficultsocial questions. She deals head-on with xenophobia, anti-Semitism, immigration, assimilation, ethnicity, multiculturalism, and the national self-image of Swedes as reflected in their cinema. She also analyzes the manner in which Swedish film represents the persecution of Jews in Nazi-dominated Europe." -- Provided by publisher.
Anti-Semitic images -- The war years: cinematic refugees -- An indigenous pariah group: The Tattare -- The Sami and the Finns -- An evolving conscience and consciousness -- Jewish figures in the films of Ingmar Berman -- The new Swedes -- The Jewish Renaissance.
Filmography: pages 399-401.
Includes bibliographical references (pages 435-441) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Jews in motion pictures; Minorities in motion pictures; Motion pictures -- Sweden -- History; Juifs au cinéma.; Minorités au cinéma.; Cinéma -- Suède -- Histoire; PERFORMING ARTS -- Film & Video -- Reference; Jews in motion pictures; Minorities in motion pictures; Motion pictures; Sweden; Filmkunst; Joden; Minderheden; Beeldvorming; Film; Music, Dance, Drama & Film; History